Measurement of thermal diffusivity of ZnO and ZnO/CuO using photoacoustic - Lo, Chee Yee.
The study is mainly based upon the measurements of thermal diffusivity by using the non-destructive photoacoustic technique. Closed Photoacoustic Cell (CPC) detector was used to determine thermal diffusivities for pure zinc oxides, 99mol%ZnO+1mol%CuO and 98mol%ZnO+2mol%CuO at different sintering temperatures and different sintering time. All of the samples are in pellet form with thickness not more than 0.5mm. The sample absorbed light energy from a He-Ne laser and caused a periodic heat flow in the sample. Acoustic signal which is generated by the sample was then detected by an electret microphone. The measurement of the photoacoustic signal as a function of the modulated frequency in the region where thermal diffusion length equals to the sample thickness. The measurement was carried out at room temperature. Thermal diffusivity of pure ZnO obtained was 0.0828 cm2/s which shows good agreement with previously reported (0.08347 cm2/s). In general, sintered pure ZnO and sintered ZnO+Cuo in different concentration gave lower values of thermal diffusivity compared to those measured at room temperature.